4 Anti-retinoblastoma protein antibodies are negatively associated with lupus nephritis. (April 2019) - Li, Jessica; Goules, Andreas; Goldman, Daniel; Rosen, Antony; Casciola-Rosen, Livia; Petri, Michelle
Abstract : Background: Retinoblastoma protein (RB) regulates nucleosome/chromatin structures and is linked to tumor suppression. It regulates the cell cycle by repression of E2F transcription factor and stabilization of heterochromatin. Because SLE is the prototypic autoimmune disease with autoantibodies against the nucleosome and chromatin, the presence of anti-RB antibodies and the association with disease manifestations were examined. Methods: 222 SLE patients from the Hopkins longitudinal cohort seen consecutively in clinic were studied (85% female, 94% Caucasian, mean age 51 years). Anti-RB antibodies were assayed by immunoprecipitation of 35S-methionine-labeled protein generated by in vitro transcription and translation from full length human cDNA. Odds ratios and p-values for univariate analyses were calculated using Fishers exact t-test. Exact logistic regression and odds ratios were calculated for the multi-variate model due to a cell frequency of zero for proteinuria ever and positive anti-RB antibody status. Results: Anti-RB antibodies were present in 8.6% of these SLE patients, 6.3% with medium-high titer. Univariate associations with SLE manifestations for the medium-high titer positive patients are included in table 1 . Of note, medium/high titer anti-RB antibodies were never found in patients with proteinuria (p=0.0028). In a multi-variate model for proteinuria, anti-RB antibodies remained negatively associated (OR 0.1112, p=0.016) after correction for female gender (OR 0.417, p=0.0498), ethnicity (Caucasian, OR 0.288, p=0.0833), low anti-dsDNA ever (OR 1.806, p=0.1192), anti-Sm positive ever (OR 1.273, p=0.7127) and low complement ever (OR 2.111, p=0.0377). Conclusions: Anti-RB antibodies are a novel specificity not previously described in SLE. These antibodies are strongly negatively associated with lupus nephritis, even in multivariate models that include other variables (female gender, Caucasian ethnicity, anti-dsDNA, anti-Sm, and low complement). Intriguingly, anti-RB antibodies are positively associated with stroke in SLE. Additional studies are warranted to understand the mechanism of this finding. Funding Source(s): The Hopkins Lupus Cohort was funded by NIH Grant R01-AR069572.